PROFIL TUGAS PERKEMBANGAN MAHASISWA PRODI PENDIDIKAN KIMIA UNIVERSITAS SULTAN AGENG TIRTAYASA - Deasy Yunika Khairun; Ibrahim Al Hakim (Jurnal Penelitian Bimbingan dan Konseling, 2019)
Research on Profile of Achievement of Tasks of Second Semester Student Development Chemistry Study Program Teacher Training and Education Faculty of the University of Sultan Ageng Tirtayasa formulated a profile of student groups in eleven aspects of development. The study aims to determine the level of group development in eleven aspects of student development in the form of frequency distribution of task achievement, highest grain picture, and lowest grain picture. The research method used is descriptive quantitative research method to obtain an empirical picture. The study population was second semester students in the Chemistry  Study Program at the Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University. The research subjects used saturated sampling techniques, namely all second semester students of the Chemistry Study Program. The tool for collecting data on the achievement profile of development tasks is the Development Task Inventory using the Development Task Analysis software or ATP version 3.5. Research results in achieving student development tasks at a thorough level. By group, the highest eight items of students are at the individualistic and thorough level. While the lowest eight items of students are at the level of self-awareness and thoroughness. Keywords: Students, development task, chemisty